1999
DOI: 10.1136/gut.45.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast proliferation, fibrosis, and defective pancreatic repair induced by cyclosporin in rats

Abstract: Background-Full recovery is always achieved after caerulein induced pancreatitis. Cyclosporin stimulates transforming growth factor (TGF-) and may interfere with pancreatic regeneration. Aim-To investigate the eVects of cyclosporin after caerulein induced pancreatitis or after caerulein injury. (Gut 1999;45:269-277) Methods-Protocol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 49 publications
2
37
2
1
Order By: Relevance
“…To test the potential benefits of tocotrienols on chronic pancreatitis, we discarded the model we had previously described because we found that cyclosporin A inhibits tocotrienol-induced cell death in vitro (38,48). Some other experimental models induce the development of chronic-like pancreatitis after surgical manipulations (35), after administration of toxic compounds that also affect other organs (43), or under specific genetic backgrounds (29).…”
Section: Discussionmentioning
confidence: 99%
“…To test the potential benefits of tocotrienols on chronic pancreatitis, we discarded the model we had previously described because we found that cyclosporin A inhibits tocotrienol-induced cell death in vitro (38,48). Some other experimental models induce the development of chronic-like pancreatitis after surgical manipulations (35), after administration of toxic compounds that also affect other organs (43), or under specific genetic backgrounds (29).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, cyclosporine interferes with the reparative process activated after experimental pancreatitis, at least in part, by inhibiting acinar cell proliferation (31). Because of the short lifetime of dispersed nonimmortalized pancreatic acinar cells, we used AR42J cells, an established model system, to investigate the biology of isolated pancreatic acinar cells (32).…”
mentioning
confidence: 99%
“…Recent studies have indicated that pancreatic stellate cells also undergo a similar transformation to a myofibroblast phenotype during pancreatic fibrosis (Bachem et al, 1998). When activated, the pancreatic myofibroblasts proliferate and generate a large amount of extracellular matrix materials including fibril-forming collagens, fibronectin, and ␣-SMA (Vaquero et al, 1999;Masamune et al, 2003). TGF-␤ plays a dominant role in the development of fibrosis in a number of organs and directly stimulates myofibroblast transformation (e.g., Overall et al, 1989).…”
Section: Discussionmentioning
confidence: 99%